Luc's abscess: a real textbook description - Liyana, Ghazali; Salman, Amiruddin; Khairudin, Abdullah (2019)
Luc’s abscess is an uncommon suppurative complication of otitis media. Unlike other extracranial abscesses, the pathogenesis of Luc's abscess is different from other extracranial complications of middle-ear infections in that it is not associated with mastoid involvement which results in subperiosteal pus formation. We present an unusual case of a 47 years old gentleman diagnosed with Luc’s abscess with mastoid involvement and describe the successful management. He presented with right temporal swelling associated with fever, right ear pain and right ear discharge. High resolution computed tomography (CT) temporal and brain confirmed hypodense collection is seen at right parieto-temporal-occipital scalp and soft tissue density within right mastoid cavity with communication between both. Incision and drainage and right cortical mastoidectomy was done. Post-operative recovery was uneventful and the patient was discharged on the tenth day post-operation after completed 10 days of intravenous antibiotic. Follow-up at 2 weeks showed complete regression of the Luc’s abscess.